Continuous ambulatory peritoneal dialysis-associated Histoplasma capsulatum peritonitis: a case report and literature review - Thanat Ounsinman; Piriyaporn Chongtrakool; Nasikarn Angkasekwinai (BMC Infectious Diseases, 2020)
Abstract Background Fungal peritonitis (FP) is a rare complication of peritoneal dialysis. We herein describe the second case in Asia of Histoplasma capsulatum peritonitis associated with continuous ambulatory peritoneal dialysis (CAPD). Case presentation An 85-year-old woman with end-stage renal disease (ESRD) who had been on CAPD for 3 years and who had a history of 3 prior episodes of peritonitis presented with intermittent abdominal pain for 2 weeks and high-grade fever for 3 days. Elevated white blood cell (WBC) count and rare small oval budding yeasts were found in her peritoneal dialysis (PD) fluid. From this fluid, a white mold colony was observed macroscopically after 7 days of incubation, and numerous large, round with rough-walled tuberculate macroconidia along with small smooth-walled microconidia were observed microscopically upon tease slide preparation, which is consistent with H. capsulatum. The peritoneal dialysis (PD) catheter was then removed, and it also grew H. capsulatum after 20 days of incubation. The patient was switched from CAPD to hemodialysis. The patient was successfully treated with intravenous amphotericin B deoxycholate (AmBD) for 2 weeks, followed by oral itraconazole for 6 months with satisfactory result. The patient remains on hemodialysis and continues to be clinically stable. Conclusion H. capsulatum peritonitis is an extremely rare condition that is associated with high morbidity and mortality. Demonstration of small yeasts upon staining of PD fluid, and isolation of slow growing mold in the culture of clinical specimen should provide important clues for diagnosis of H. capsulatum peritonitis. Prompt removal of the PD catheter and empirical treatment with amphotericin B or itraconazole is recommended until the culture results are known.